INOVASI KURIKULUM LITERASI DIGITAL BERBASIS GAMIFIKASI UNTUK SISWA BERKEBUTUHAN KHUSUS DI SEKOLAH DASAR INKLUSIF - Wizerti Ariastuti Saleh; Siti Raihan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
AbThis study explores the implementation of a gamification-based digital literacy curriculum for students with special needs at SDN Unggulan Mongisidi 1 Makassar. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and FGD with the principal, special assistant teachers, classroom teachers, students, and parents. Data were analyzed using the Miles, Huberman, and Saldaña model. The findings reveal three main results: (1) implementation follows five stages: planning, socialization, phased application of gamification elements (points, badges, leaderboards, levels, challenges), individual assistance, and continuous evaluation; (2) student responses were highly positive with 100% enthusiasm, increased focus (ADHD students from 15 to 40 minutes), and improved learning independence; (3) challenges include limited devices and teacher preparation time, while support comes from school leadership, teacher collaboration, and parent participation. This study provides a contextual understanding of gamification curriculum implementation in inclusive elementary schools.